Another Look at Anonymous Communication - Lai, Russell W. F.; Cheung, Kam-Fung; Chow, Sherman S. M.; So, Anthony Man-Cho (IEEE Transactions on Dependable and Secure Computing, 2019)
Anonymous communication is desirable for personal, financial, and political reasons. Despite the abundance of frameworks and constructions, anonymity definitions are usually either not well defined or too complicated to use. In between are ad-hoc definitions for specific protocols which sometimes only provide weakened anonymity guarantees. This paper addresses this situation from the perspectives of syntax, security definition, and construction. We propose simple yet expressive syntax and security definition for anonymous communication. Our syntax covers protocols with different operational characteristics. We give a hierarchy of anonymity definitions, starting from the strongest possible to several relaxations. We also propose a modular construction from any key-private public-key encryption scheme, and a new primitive-oblivious forwarding protocols, of which we give two constructions. The first is a generic construction from any random walk over graphs, while the second is optimized for the probability of successful delivery, with experimental validation for our optimization. Anonymity is guaranteed even when the adversary can observe and control all traffic in the network and corrupt most nodes, in contrast to some efficient yet not-so-anonymous protocols. We hope this work suggests an easier way to design and analyze efficient anonymous communication protocols in the future.
CRIS-Team WoS Importer:2019-09-20